In court and kampong tales & sketches of native life in the Malay peninsula - Clifford, Hugh Charles Sir 1866-1941 (Silverfish Malaysian classics, 2019)
The nineteen tales and sketches, which are enclosed within the covers of this book, relate to certain brown men and obscure things in a distant and very little known corner of the Earth. The Malay Peninsula - that slender tongue of land which projects into the tepid seas at the extreme south of the Asiatic Continent - is but little more than a name to most dwellers in Europe. But, even in the peninsula itself, and to the majority of those white men whose whole lives have been passed in the Straits of Malacca, the East Coast and the remote interior, of which I chiefly write, are almost as completely unknown.